PERANCANGAN ALAT SISTEM PENGIRIMAN PESAN SMS MELALUI JALUR RADIO KOMUNIKASI - Setyaningsih, Endah; Winata, Tony; Nugroho, Koko (Universitas Tarumanagara, 2006)
The part of transmitter is in the police station for sending the message, if that message was received so buzzer will sound overall with the message was displayed on LCD. The system is designed for announcement to police who didn’t in his her car with easily.